Comparative study of Bi-Te-Se-S mineralizations in Slovak Republic and Transcarpathian region of Ukraine. Part 2. Crystal chemistry and genesis of layered Bi-tellurides - Melnikov, V.; Jeleň, S.; Bondarenko, S.; Balintová, T.; Ozdín, D.; Grinchenko, A. (Мінералогічний журнал, 2010)
Bismuth tellurides of layered structure (tetradymite group) are characteristic minerals of metasomatically altered neovolcanites of Slovakia and Ukrainian Transcarpathians. Tsumoite, pilsenite and joseite (A and B) are established in both regions, but the tetradymite is not found in Transcarpathians. Two new minerals, telluronevskite and vihorlatite, are found in Slovakia. Phase Ві2Те (X-ray, microprobe) that forms epitaxial intergrowths with pilsenite is determined in Transcarpathians (Il'kivtsy). Se-joseite-В, Se-tsumoite, Te-bismuthite, phase ~ Ві2SeS (intermediate phase between nevskite and ingodite) and phase with stoichiometry of А3Х2 (A = Bi; Х = Te, Se, S) are determined in globules of native bismuth (Smerekiv Kamin') by microprobe analysis, but the number of anions Х varies from Bi3Te1.5S0.5 to Bi3TeSe0.5S0.5. The temperature of formation of layered bismuth tellurides is estimated within the interval 350—100 ºС.